EMPATHY AND HAPPINESS OF DISASTER VOLUNTEERS - Sofia Nuryanti (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2020)
The disaster that occurred did not rule out the possibility of causing casualties. Every disaster event requires the assistance of volunteers in helping with post-disaster management. This study examines the happiness of disaster volunteers in terms of empathy. The quantitative approach is used in this study to determine the role of empathy on disaster volunteer happiness using linear regression analysis. Using accidental sampling, as many as 135 disaster volunteers were at least 18 years old and had helped the disaster evacuation process. The regression analysis results show that empathy can significantly predict the happiness of disaster volunteers. The regression results also show that the role of empathy contributes 33% of the variance in the happiness of disaster volunteers.